Treatment of domestic wastewater by electrocoagulation in a cell with Fe-Fe electrodes - Kurt, Ugur; Gonullu, M. Talha; Ilhan, Fatih; Varinca, Kamil (MARY ANN LIEBERT, INC, 2008)
In this study, the potential to treat domestic wastewater ( DWW) using an electrocoagulation ( EC) process was tested on two different samples, one of which was heavily loaded [ 380 mg chemical oxygen demand ( COD)/ L]; the other was weakly loaded [ 260 mg COD/ L]. The samples were supplied from the Istanbul-Yenikapi DWW pretreatment plant. The experimental studies were conducted within an electrolysis cell with Fe-Fe electrodes. In this cell, under optimum operational conditions in the form of electrical power and electrolysis time, pollutant removal efficiency ( as COD), suspended solids ( SS) and characteristics of formed sludge were tested. At the end of these studies, the optimum operational conditions found for electrical power was 0.6 W for both DWW samples, and electrolysis times were determined as 15 min for heavily loaded DWW ( HLDWW) and 8 min for weakly loaded DWW ( WLDWW). Energy consumption in optimum electrical charge conditions was 0.4 kWh/m(3) HLDWW and 0.2 kWh/ m(3) WLDWW. The removal efficiency of COD and SS were obtained and shown to be over 60 and 70%, respectively. The level of sludge production was 1.5-2% during the optimal reaction time, and sludge volume was decreased 50% using H2O2.
Keywords: COD; domestic wastewater; electrocoagulation; electricity consumption; sludge reduction; Engineering; Environmental Sciences & Ecology